Immunogenic Cell Death Induction by Ionizing Radiation - Zhu, Mengqin; Yang, Mengdie; Zhang, Jiajia; Yin, Yuzhen; Fan, Xin; Zhang, Yu; Qin, Shanshan; Zhang, Han; Yu, Fei (Frontiers in Immunology, 2021)
Immunogenic cell death (ICD) is a form of regulated cell death (RCD) induced by various stress and produces antitumor immunity via damage-associated molecular patterns (DAMPs) release or exposure, mainly including high mobility group box 1 (HMGB1), calreticulin (CRT), adenosine triphosphate (ATP) and heat shock proteins (HSPs). Emerging evidence has suggested that ionizing radiation (IR) can induce ICD, and the dose, type and fractionation of irradiation influence the induction of ICD. At present, IR-induced ICD is mainly verified in vitro and mice and there is few clinical evidence about it. To boost the induction of ICD by IR, some strategies have shown synergy with IR to enhance antitumor immune response, such as hyperthermia, nanoparticles and chemotherapy. In this review, we focus on the molecular mechanisms of ICD, ICD-promoting factors associated with irradiation, the clinical evidence of ICD and immunogenic forms of cell death. Finally, we summarize various methods of improving ICD induced by IR.